IMPLEMENTASI FISHBONE DIAGRAM DALAM ANALISIS BREAKDOWN DIVISI MAINTENANCE LISTRIK PADA PRODUKSI BAJA DI PT X - Rizdam Firly Muzakki; Nuralam; Sri Lestari Kusumastuti (INKOFAR, 2025)
Breakdown time is one of the events that must be minimized, even eliminated in every production process in the manufacture sector. PT X as one of the national steel producers also strives to optimize the production process, considering that the capital needed to produce steel is relatively high. Breakdown time needs to be analysed properly to get the right and accurate solution. One of the tools that can be used is fishbone diagram. Based on the data obtained, it is known that the two most dominant obstacles that occurred during the December - May period occurred in the Crop Shear and Flying Shear areas. In the Crop Shear area, it is known that the motor trips due to indications of overspeed, while in the Flying Shear area the motor works abnormally due to indications of a dead oil pump. Maintenance and repair actions are then designed based on the results of the analysis obtained to anticipate the original occurrence in the future through corrective and preventive maintenance.